Foraging behavior of wood mice as related to presence and activity of genets (JOURNAL OF MAMMALOGY, 2005)
Predators influence the distribution of prey directly if predation reduces local population density, or indirectly if the presence of predators induces behavioral or physiological responses to predation risk. We analyzed whether the foraging behavior of wood mice (Apodemus sylvaticus) was affected by the presence and activity of small-spotted genets (Genetta genetta) at ``risky{''} baiting stations monitored with automatic cameras. Sampling stations in 6 x 6 grids spaced at 250 m were arranged in 3 habitat types (shrubland, pine woodland, and holm oak woodland). Grids were sampled systematically by means of groups of 2-9 cameras monitoring sampling stations during a week. We obtained 377 independent contacts of wood mice and 35 independent contacts of at least 8 different genets. Patterns of habitat use by genets and wood mice were spatially discordant, because only 2 cameras detected both. Wood mice visited baits more often and during longer periods in groups of sampling stations where genets were not detected than in groups where genets were detected within the same week. Mean time spent foraging by genets negatively influenced both the number of foraging bouts per night and the mean duration of such bouts by mice using nearby baits. Finally, temporal patterns of activity of mice along the night were different depending on whether genets were foraging nearby. Temporal patterns of mice when and where genets were absent were positively correlated with patterns of genet activity, whereas mice patterns were negatively correlated with genet patterns when and where genets were present. Sampling dates, habitat types, and moonlight levels did not seem to have influenced these results. Wood mice showed spatial and temporal changes in foraging behavior in response to the presence of genets, and decisions about how often and how long to forage were affected by foraging activity of genets. Results obtained provided direct evidence of a foraging game of stealth and fear between mice and their predator that could help to explain mice distribution in Mediterranean postfire habitats.

Diversidad biológica y sostenibilidad ecológica y económica de los sistemas adehesados (Ecosistemas, 2003)
Los bosques mediterráneos son sistemas naturales con una elevada diversidad biológica, que tiende a aumentar cuando son explotados para formar dehesas arboladas. Dentro de este sistema de explotación, la riqueza de especies varía en función de los efectos del manejo humano sobre la estructura de la vegetación, tanto subarbórea (presencia de cultivos de cereal o manchas de matorral) como arbórea (densidad de árboles). Estas tendencias se observan en varios grupos de organismos y para un amplio rango de escalas espaciales, y parecen deberse a la íntima coexistencia espacial en las dehesas de elementos faunísticos y florísticos forestales, asociados al arbolado y al matorral, y de elementos propios de zonas abiertas, asociados a los pastizales y cultivos sobre los que crecen los árboles. La coexistencia a escala de finca de distintos usos, así como la coexistencia de las dehesas y otros hábitats a escala regional, contribuyen al mantenimiento de especies adicionales. No obstante, se requieren perturbaciones como el fuego o el uso humano, que serían las causas últimas de esta diversidad. La diversidad biológica de las dehesas podría contribuir a su sostenibilidad económica si èsta es valorada adecuadamente por la sociedad. Además, se requerirían medidas adicionales que garantizasen situaciones temporales de menor diversidad pero indispensables para la regeneración del arbolado y la sostenibilidad ecológica de este peculiar sistema de explotación.

Effects of forest fragmentation on the winter body condition and population parameters of an habitat generalist, the wood mouse Apodemus sylvaticus: a test of (Acta Oecologica, 1999)
Three main causal hypotheses have been proposed to explain the inverse relationships between habitat patch size and density of gen- eralist mouse species in fragmented habitats: 1) enhanced habitat conditions as habitat patch size decreases; 2) inhibited emigration of excess indi- viduals in small and isolated habitat patches; and 3). reduced territoriality in small patches because they are occupied temporarily by non- reproductive individuals. From the mechanism underlying each hypothesis, we derived predictions on the effects of fragment size on the body condition of individuals (measured both as absolute body size and as body mass relative to body size) and some demographic parameters of mouse populations redated to reproductive output (sex-ratio and proportions of sexually active and recently-born individuals), and we tested such predic- tions with data from wood mice Apodemus sylvaticus wintering in three Spanish forest archipelagos in which the inverse relationship between for- est patch size and mouse abundance had been previously proven. No differences in average body size or in average body mass relative to body size were detected among fragments. Mouse populations wintering in small fragments showed more male-biased sex-ratios, a larger proportion of sex- ually active adults and fewer juveniles as compared to mouse populations wintering in large fragments nearby. Results clearly rejected the third hypothesis and did not support the second one. It thus seemed that habitat conditions for mice improved as forest fragment size decreased, although the expected positive effects on individuals could have been prevented by relaxed territoriality and increased food resource depletion by denser mouse populations. Bearing in mind the negative effects of dense wood mice populations on the distribution, abundance and population dynamics of forest species, this apparent enhancement of habitat conditions for mice in small forest fragments could have far-reaching conse- quences for the long-term persistence of such fragments.

Linking individual foraging behavior and population spatial distribution in patchy environments: a field example with Mediterranean blue tits (Oecologia, 1997)
In spite of recent theoretical interest, few field studies have addressed the links between individual behavioral decisions and population distribution. This work analyzes the foraging behavior of individuals and the spatial distribution of a population of blue tits (Parus caeruleus) just before the main breeding season, when blue tit foraging was not affected by central-place or flocking behaviors. The study was carried out in open holm oak Quercus ilex woodlands (dehesas) that are patchy for canopy-foraging birds because of the scattered arrangement of trees. Residence time on each tree was not correlated either with previous flight time or with prey abundance in trees. Flight distances between trees were larger than average distances estimated in random samples of holm oaks taken close to foraging birds. Trees were not selected by birds on the basis of their expected energy costs and rewards. Bird abundance was not related to food availability in trees or to tree size across dehesas. However, bird abundance was strongly correlated with tree density and with the availability of tree holes for nesting, to the extent that the proportion of tits matched the proportions of both tree abundance and hole abundance across study plots. Overall, neither the behavior of individuals nor the distribution of the population of blue tits corresponded with food resources, which appeared superabundant; instead, tits appeared to behave and be distributed according to the distribution of structural resources such as trees and tree holes for nesting.

Habitat selection patterns of common cranes Grus grus wintering in holm oak Quercus ilex dehesas of central Spain: Effects of human management (Biological Conservation, 1996)
Most of the western European population of common cranes Grus grus spends the winter in Iberian wooded dehesas, a kind of wood-pasture composed of grasslands, cereal croplands and Mediterranean scrub, densely inter- spersed with holm oak trees Quercus ilex in a savanna- like landscape. Three main types of wooded dehesas can be distinguished according to management." grazed dehesas, shrubby dehesas with occasional grazing, and cultivated dehesas without livestock. Cranes depend largely on acorns during winter and mainly select dehesas cultivated with cereals where acorn abundance is not reduced by livestock. Apparent positive effects of livestock on earth- worm abundance, the main alternative food source for cranes, does not compensate for acorn depletion. Thus, any increase in livestock grazing pressure would have a strong impact on European crane populations during their wintering in Spain.

EFFECTS OF FOOD ABUNDANCE AND HABITAT STRUCTURE ON SEED-EATING RODENTS IN SPAIN WINTERING IN MAN-MADE HABITATS (ZEITSCHRIFT FUR SAUGETIERKUNDE-INTERNATIONAL JOURNAL OF MAMMALIAN BIOLOGY, 1993)
The patterns of abundance and seed (acorn) predation races were analyzed in granivorous rodents (mainly the wood mouse Apodemus sylvaticus L.) wintering in two man-made habitats: cereal croplands, and a kind of wood-pasture exclusive to the western Mediterranean basin, the dehesas. Both seed (acorn) abundance ana vegetation structure were also measured. Within dehesas, neither rodent abundance nor acorn predation rates were related to acorn abundance, whereas there Tvas a significant. association between rodent abundance and shrub cover at the end of winter. These results were coincident with previous findings in croplands. Both rodent abundances and seed predation rates were lower in dehesas than in croplands, despite the better structural and trophic conditions of the first habitat for rodents (larger shrub cover and food abundance). However, the body condition of animals was better in dehesas, to the extent that we found strong evidence for mincer reproduction. Rodent predator communities appear to be more diverse and denser in dehesas than in croplands. This suggests a heavier predation pressure in dehesas which would have culled rodent populations in such a way chat food Tvas plentiful for survivors, rhus explaining their scarcity, good body condition, and low dependence on food resources.
APS